Linked color imaging reduces the miss rate of neoplastic lesions in the right colon: a randomized tandem colonoscopy study - Paggi, Silvia; Mogavero, Giuseppe; Amato, Arnaldo; Rondonotti, Emanuele; Andrealli, Alida; Imperiali, Gianni; Lenoci, Nicoletta; Mandelli, Giovanna; Terreni, Natalia; Conforti, Francesco Simone; Conte, Dario; Spinzi, Giancarlo; Radaelli, Franco (Endoscopy, 2018)
Background Linked color imaging (LCI) is a newly developed image-enhancing endoscopy technology that provides bright endoscopic images and increases color contrast. We investigated whether LCI improves the detection of neoplastic lesions in the right colon when compared with high definition white-light imaging (WLI).Methods Consecutive patients undergoing colonoscopy were randomized (1:1) after cecal intubation into right colon inspection at first pass by LCI or by WLI. At the hepatic flexure, the scope was reintroduced to the cecum under LCI and a second right colon inspection was performed under WLI in previously LCI-scoped patients (LCI–WLI group) and vice versa (WLI–LCI group). Lesions detected on first- and second-pass examinations were used to calculate detection and miss rates, respectively. The primary outcome was the right colon adenoma miss rate.Results Of the 600 patients enrolled, 142 had at least one adenoma in the right colon, with similar right colon adenoma detection rates (r-ADR) in the two groups (22.7 % in LCI–WLI and 24.7 % in WLI–LCI). At per-polyp analysis, double inspection of the right colon in the LCI–WLI and WLI–LCI groups resulted in an 11.8 % and 30.6 % adenoma miss rate, respectively (P < 0.001). No significant difference in miss rate was found for advanced adenomas or sessile serrated lesions. At per-patient analysis, at least one adenoma was identified in the second pass only (incremental ADR) in 2 of 300 patients (0.7 %) in the LCI – WLI group and in 13 of 300 patients (4.3 %) in the WLI – LCI group (P = 0.01).Conclusions LCI could reduce the miss rate of neoplastic lesions in the right colon.